The Histological and Immunohistochemical Aspects of Bile Reflux in Patients with Gastroesophageal Reflux Disease. (21st July 2011) - Nakos, Andreas; Kouklakis, Georgios; Pitiakoudis, Michail; Zezos, Petros; Efraimidou, Eleni; Giatromanolaki, Alexandra; Polychronidis, Alexandros; Liratzopoulos, Nikolaos; Sivridis, Efthimios; Simopoulos, Konstantinos
Abstract : Introduction . The pathogenesis of GERD is strongly related with mixed acid and bile reflux. Benign and malignant esophageal and gastric lesions have been associated with synergetic activity between those parameters. Bile reflux causes reactive gastropathy evaluated with Bile Reflux Index (BRI). The aim was to investigate if the sequence: bile reflux-intestinal metaplasia-GERD-esophagitis, is associated with apoptotic/oncogenetic disturbances. Materials/Methods . Fifteen asymptomatic subjects and 53 GERD patients underwent gastroscopy with biopsies. The specimens examined histologically and immunohistochemically for p53, Ki-67, Bax, and Bcl-2. Results . Elevated BRI score detected in 47% (25/53) of patients with GERD and in 13% (2/15) of controls (P = 0.02 ). Severe esophageal lesions were significantly more common in BRI (+) patients (14/25) compared to BRI (−) ones (P = 0.0049 ). Immunohistochemical analysis did not show associations between BRI score and biomarker expression. Conclusions . Bile reflux gastropathy is associated with GERD severity, but not with oncogene expression or apoptotic discrepancies of the upper GI mucosa.